The "Humivent" device for rising damp treatment - Vasco Peixoto De Freitas (2011)
Humidity is one of the main causes of decay in buildings, particularly rising damp. The treatment of this phenomenon in historical buildings is very complex due to the thickness and heterogeneity of the walls. Moisture transfer in the walls of historical buildings is in direct contact with the ground leads to the migration of soluble salts, which are responsible for many building pathologies. Traditional methods of dealing with this problem (chemical or physical barriers, electro-osmosis, etc) have proved to be somewhat ineffective or are too expensive. In the recent years, experimental and in-field research into the effectiveness of wall base ventilation systems (natural or hygro-regulated-HUMIVENT device) to reduce the level of rising damp, conducted at the Building Physics Laboratory, Faculty of Engineering, University of Porto, has yielded interesting results. This paper presents recent patents and publications in the rising damp area and describes a new system called HUMIVENT for treating rising damp in historical buildings based upon a hygro-regulated wall base ventilation system. Finally, we analyse the results obtained in laboratory and the following implementation of the system in a church in Northern Portugal. It was a defined criteria to avoid condensation problems inside the system and crystallizations/dissolution problems at the walls. Â(c) 2011 Bentham Science Publishers.